2020
DOI: 10.3390/ijms21093228
|View full text |Cite
|
Sign up to set email alerts
|

Short-Term Physiological Effects of a Very Low-Calorie Ketogenic Diet: Effects on Adiponectin Levels and Inflammatory States

Abstract: Adipose tissue is a multifunctional organ involved in many physiological and metabolic processes through the production of adipokines and, in particular, adiponectin. Caloric restriction is one of the most important strategies against obesity today. The very low-calorie ketogenic diet (VLCKD) represents a type of caloric restriction with very or extremely low daily food energy consumption. This study aimed to investigate the physiological effects of a VLCKD on anthropometric and biochemical parameters such as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
62
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(68 citation statements)
references
References 46 publications
6
62
0
Order By: Relevance
“…1 that insulin levels were similar in all groups, whereas LC and KD significantly increased adiponectin. The results were consistent with previous study, which found the level of adiponectin was elevated under the stimulation of KD [24]. However, LCKD1 (containing MCFAs) had the opposite effect, suggesting that MCFAs could counteract the KD effect on adiponectin.…”
Section: Discussionsupporting
confidence: 93%
“…1 that insulin levels were similar in all groups, whereas LC and KD significantly increased adiponectin. The results were consistent with previous study, which found the level of adiponectin was elevated under the stimulation of KD [24]. However, LCKD1 (containing MCFAs) had the opposite effect, suggesting that MCFAs could counteract the KD effect on adiponectin.…”
Section: Discussionsupporting
confidence: 93%
“…The effect was a significant decrease in body weight, body mass index, waist circumference, hip circumference, body fat %, and decreased fasting leptin levels. Similar positive outcomes were seen in other KD diet studies [ 56 , 63 , 64 ]. Similarly, a recent meta-analysis concluded that very low-calorie ketogenic diets are a very effective strategy for treating obesity [ 65 ].…”
Section: The Effect Of the Ketogenic Diet On Weight Losssupporting
confidence: 88%
“…Most adiponectin presents in the serum as an oligomer, including low molecular weight (LMW), medium molecular weight (MMW), and high molecular weight (HMW). 3 Among them, HMW is considered as the most biologically active. Serum adiponectin concentration ranges widely in healthy adults.…”
Section: Discussionmentioning
confidence: 99%
“…Monda et al found that adiponectin concentration mean in people with obesity was 10.8 μg/mL with a standard deviation of 1.2 (10.8±1.2), which could be increased to 25.55±1.3 μg/mL by a very low-calorie ketogenic diet. 3 From the above evidences, it is suggested that the functions of adiponectin are closely associated with its concentrations. Moreover, Negoro et al found that low adiponectin concentration is responsible for the systemic inflammation in adiponectin anti-sense transgenic mice.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation